Studi Kelayakan Kurikulum Pendidikan Vokasional Agribisnis untuk Peningkatan Keterampilan Manajerial Petani - Yunita Widia Putri; Ihsan Mustofa; Ainun Silvi Asya; Bambang Irawan; Gama Setyadzi (CV. Creative Tugu Pena, 2021)
This study aims to emphasize the importance of equipping farmers with enhanced capabilities to maximize the potential of their available resources. As one of the foundational pillars of national development, farmers play a critical role in ensuring food security through their agribusiness activities. To improve both the quantity and quality of agricultural output, effective farmer management systems must be developed based on real-world challenges faced in the field. Enhancing farmer welfare requires the optimal application of modern and renewable scientific knowledge. This research adopts a qualitative, literature-based approach, drawing on peer-reviewed scientific references and prior studies. The findings highlight that improving farmer performance depends on several key factors: skill development, increased discipline, enhanced productivity, and better overall management practices. This study contributes to the body of knowledge by synthesizing prior research into a practical framework for enhancing farmer performance. It offers insights for policymakers, agricultural trainers, and development practitioners on how to structure farmer empowerment programs rooted in field realities and scientific evidence.